A Novel Neuraminidase Virus-Like Particle Vaccine Offers Protection Against Heterologous H3N2 Influenza Virus Infection in the Porcine Model - Pliasas, Vasilis C.; Menne, Zach; Aida, Virginia; Yin, Ji-Hang; Naskou, Maria C.; Neasham, Peter J.; North, J. Fletcher; Wilson, Dylan; Horzmann, Katharine A.; Jacob, Joshy; Skountzou, Ioanna; Kyriakis, Constantinos S. (Frontiers in Immunology, 2022)
Influenza A viruses (IAVs) pose a global health threat, contributing to hundreds of thousands of deaths and millions of hospitalizations annually. The two major surface glycoproteins of IAVs, hemagglutinin (HA) and neuraminidase (NA), are important antigens in eliciting neutralizing antibodies and protection against disease. However, NA is generally ignored in the formulation and development of influenza vaccines. In this study, we evaluate the immunogenicity and efficacy against challenge of a novel NA virus-like particles (VLPs) vaccine in the porcine model. We developed an NA2 VLP vaccine containing the NA protein from A/Perth/16/2009 (H3N2) and the matrix 1 (M1) protein from A/MI/73/2015, formulated with a water-in-oil-in-water adjuvant. Responses to NA2 VLPs were compared to commercial quadrivalent whole inactivated virus (QWIV) swine IAV vaccine. Animals were prime boost vaccinated 21 days apart and challenged four weeks later with an H3N2 swine IAV field isolate, A/swine/NC/KH1552516/2016. Pigs vaccinated with the commercial QWIV vaccine demonstrated high hemagglutination inhibition (HAI) titers but very weak anti-NA antibody titers and subsequently undetectable NA inhibition (NAI) titers. Conversely, NA2 VLP vaccinated pigs demonstrated undetectable HAI titers but high anti-NA antibody titers and NAI titers. Post-challenge, NA2 VLPs and the commercial QWIV vaccine showed similar reductions in virus replication, pulmonary neutrophilic infiltration, and lung inflammation compared to unvaccinated controls. These data suggest that anti-NA immunity following NA2 VLP vaccination offer comparable protection to QWIV swine IAV vaccines inducing primarily anti-HA responses.